(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
As result of facial-paleogeographic studies of the Paleogene deposits of the Fergana depression are distinguished underwater delta, wave-cut, shallow-bay (lagoon) and central-desilting facial belts. The article gives a detailed description of the lagoon facies with their separation into 4 types, which can be the criteria for the prospecting and exploration of nonmetallic minerals, such as palygorskite clays, dolomites and gypsum.